KONSELING KELOMPOK DALAM MEMBANGUN KEPERCAYAAN SISWA TERHADAP PENTINGNYA PENDIDIKAN PEREMPUAN DI SMA PESANTREN AL-IN’AM BANJAR TIMUR GAPURA - khazinatul fitriyah (STKIP PGRI SUMENEP, 2023)
Women’s education is the most important foundation for a nation in the formation of a brilliant generation. Therefore, women’s education needs attention and is synergistic in various components of education that can be involved both formal and informal both in school, the family sphere and the sphere public. The purpose of this research was to find out the application of group counseling in building women’s education in school and how the influence of the application of group counseling carried out at SMAP Al-In’am Banjar Timur. The type of research used in this study is a qualitative method with a descriptive approach, the process of collecting data through observation, interviews and documentation. A series of research processes that the researchers went through, this study found that from group counseling carried out by the counseling theacher, it made students have the enthusiasm to continue school, strengthened each other between group members, the student were not inferior, and most importantly they were able to work together in solving other life problems member. This can be seen from the increasing number of female students of continue on to tertiary instituations or continue to the salaf.